Juvenile Justice in Comparative Perspective: A Study of Indonesian State Law and Islamic Law - Adrian Hadiputra; Muhammad Azil Maskur; Arifin, Ridwan; Ikram Amrullah; Hibatullah Maajid (Contemporary Issues on Interfaith Law and Society, 2024)
This study examines juvenile justice systems through a comparative analysis between Indonesian State Law and Islamic Law, focusing on the treatment and legal protection of juvenile offenders. The Indonesian legal framework, which follows a secular approach, offers specific regulations for juvenile justice under the Juvenile Justice System Law (No. 11 of 2012). This law emphasizes rehabilitation and diversion, ensuring that juvenile offenders are treated differently from adults, with a focus on reintegration into society. In contrast, Islamic law, rooted in the principles of Sharia, offers a distinct approach to juvenile justice. While Islamic law does not have a unified legal code for juvenile offenders, its application emphasizes the protection of minors from harsh punishments and prioritizes their rehabilitation. Islamic legal scholars agree on the importance of age and maturity in determining the level of responsibility for a juvenile’s actions. The concept of "ta'zir" (discretionary punishment) plays a significant role in ensuring that juvenile offenders are treated with fairness, aiming at their moral and social reform. This comparative study highlights the similarities and differences between the two legal systems in addressing juvenile crime, considering the broader cultural and legal contexts that shape juvenile justice policies in Indonesia and Islamic law. The paper explores how these legal frameworks balance punishment with rehabilitation and the role of community involvement in reforming juvenile offenders. The study contributes to understanding the potential for cross-jurisdictional insights in improving juvenile justice practices, emphasizing the need for a more unified and human-centric approach in dealing with young offenders.